2021
DOI: 10.1158/1055-9965.epi-20-0833
|View full text |Cite
|
Sign up to set email alerts
|

Association between Gene Promoter Methylation and Cervical Cancer Development: Global Distribution and A Meta-analysis

Abstract: DNA methylation is the main epigenetic event for gene silencing and is associated with carcinogenesis. In this meta-analysis, we evaluated the association between the methylation of the promoter regions of APC, CADM1, CCNA1, CDH1, DAPK, FHIT, HIC1, MAL, MGMT, hMLH1, P16, PAX1, RAR-β, and RASSF1 genes and the risk of cervical cancer development and progression. Overall, 194 eligible studies were identified assessing the associations of promoter methylation status of aforementioned genes with low- and high-grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“… 167 Additionally, methylation frequency at the promoters of multiple human genes is significantly higher in cervical cancer samples than controls. 168 When considering performance on self-collected samples, one study found that the methylation levels at PAX1 , SOX1 , and ZNF582 showed no significant differences between self-collected and clinician-collected samples in specificity or sensitivity as predictors of CIN3 + . 169 However, HPV-methylation studies to date have been limited in their geographic spread and HPV types studied: most have focused on HPV16, 170 and few have been conducted in Africa, 168 despite sub-Saharan Africa having the highest incidence of cervical cancer worldwide.…”
Section: Self-sampling Beyond Hpv Testingmentioning
confidence: 99%
See 1 more Smart Citation
“… 167 Additionally, methylation frequency at the promoters of multiple human genes is significantly higher in cervical cancer samples than controls. 168 When considering performance on self-collected samples, one study found that the methylation levels at PAX1 , SOX1 , and ZNF582 showed no significant differences between self-collected and clinician-collected samples in specificity or sensitivity as predictors of CIN3 + . 169 However, HPV-methylation studies to date have been limited in their geographic spread and HPV types studied: most have focused on HPV16, 170 and few have been conducted in Africa, 168 despite sub-Saharan Africa having the highest incidence of cervical cancer worldwide.…”
Section: Self-sampling Beyond Hpv Testingmentioning
confidence: 99%
“… 168 When considering performance on self-collected samples, one study found that the methylation levels at PAX1 , SOX1 , and ZNF582 showed no significant differences between self-collected and clinician-collected samples in specificity or sensitivity as predictors of CIN3 + . 169 However, HPV-methylation studies to date have been limited in their geographic spread and HPV types studied: most have focused on HPV16, 170 and few have been conducted in Africa, 168 despite sub-Saharan Africa having the highest incidence of cervical cancer worldwide. 171 Further clinical studies with large cohorts are recommended to fully evaluate the performance of methylation assays as predictors of CIN2 + .…”
Section: Self-sampling Beyond Hpv Testingmentioning
confidence: 99%
“…Based on the clinicopathological manifestations described above, CADM1 can be utilized as a more practical clinical biomarker (Lee et al, 2013;Chen et al, 2016). The specific reason is that CADM1 is downregulated in most cases due to its promoter methylation as well as being related to the progression of malignant tumors, advanced classification, poor 5-year survival, and high recurrence rate; for example, in cervical cancer, CADM1 can be used as a biomarker to participate in the assessment of cervical epithelial lesions (Del Pino et al, 2019;El Aliani et al, 2021). A low level of CADM1 is often associated with more severe cervical lesions.…”
Section: Cadm1 As a Biomarker For Cancer Diagnosis And Prognosismentioning
confidence: 99%
“…16−18 In addition, recent work has shown that epigenetic alterations, especially hypermethylation, occur on the promoter region of FHIT gene and are associated with some cancers and noncancerous diseases, including Crohn's disease. 19,20 FHIT protein exhibits dinucleoside triphosphate hydrolase (AP 3 Aase) activity, converting diadenosine triphosphate (Ap 3 A) to adenosine monophosphate (AMP) and adenosine diphosphate (ADP) with the assistance of divalent metal cations, such as Mg 2+ or Mn 2+ . 21 However, evidence is accumulating that the catalytic activity is not necessary for the tumor-suppressor functions.…”
Section: ■ Introductionmentioning
confidence: 99%